Environmental Impact Assessment and Sedimentology of the Carbonate Quarry Site for Al-Maroua’ah Cement Plant in Al-Hodeida District, NW Yemen - Al-Mashaikie, Sa’ad Zeki A. Kader A.Kader; Al-Karraz, Abdul-Kader Mohammed (Asian Review of Environmental and Earth Sciences, 2015)
In this study, environmental impact assessment and sedimentology includes chemical analysis were carried out for the quarry site of the limestone raw material in Al-Maroua’ah cement plant in Tehama plane, Al-Hodeida district NW Yemen. The study includes the assessment of the limestone raw materials, the quality, chemical and mineralogical analysis and expected pollutions impact in the quarry site. The studied rock successions are belonging to the Amran Group, which is composed mainly of limestone rocks with few interbedded marl, shale and sandstone beds. The chemical analysis of the limestone rocks show CaO content is (50.31%), with very little MgO content (0.71%). The present shale marl and sandstone rock units are useful for the correction of the rocks to concise with the international specifications of the cement production. The site of the quarry of the main raw materials of limestone rocks was selected far From the villages and human populations to prevent the environmental pollutions according to the WHO and YEPA specifications. The emitted dust from the operations of the quarry machine makes impacts on the surrounding environments especially for the farms and the natural plants and animals, which are living in the region. For this, the site of quarry is selected in a mountain far from the vegetation, population and villages to avoid the expected environmental impact. Mitigation plan for prevent or decreases the pollution impact to the minimum, was discussed.